The drivers of trust and distrust exploring components of trustworthiness - Kavanagh, Jennifer 1981-; Carman, Katherine Grace; DeYoreo, Maria; Chandler, Nathan 1982-; Davis, Lynn E. 1943- (RAND Corporation, 2020)
Trust in many institutions, such as government and media, has declined in the past two decades. Although such trends are well documented, they are not well understood. The study described in this report presents a new framework for assessing institutional trust and understanding the individual characteristics and institutional attributes that affect trust. Analysis is based on a survey of 1,008 respondents conducted through the RAND Corporation's American Life Panel in April 2018. The study makes several key contributions to the field of institutional trust research. First, researchers used a scale that distinguishes between trust and distrust, thus allowing a different understanding of trust. Second, the analysis is a first step toward understanding why people trust institutions. The framework allows exploration of components of trustworthiness-i.e., the institutional attributes that people say they consider important to levels of trust (e.g., integrity, competence). The researchers also analyzed relationships between components of trustworthiness and the individual characteristics of those expressing the level of trust. Third, the survey featured questions about multiple institutions, allowing researchers to make comparisons across institutions. The research provides insights into individual characteristics and institutional attributes associated with institutional trust. This study is a "first cut" at a complicated concept and at exploring what is needed to rebuild institutional trust
"Contering Truth Decay: A RAND Initiative to Restore the Role of Facts and Analysis in Public Life."
Keywords: Akzeptanz; Einrichtung; Vertrauen; USA; Trust / Social aspects / United States; Trust / Political aspects / United States; United States / Politics and government / 2017-; Politics and government; Trust / Political aspects; Trust / Social aspects; United States; Since 2017